Aortic stiffness and blood pressure variability in young people: a multimodality investigation of central and peripheral vasculature. Issue 3 (March 2017) - Boardman, Henry; Lewandowski, Adam J.; Lazdam, Merzaka; Kenworthy, Yvonne; Whitworth, Polly; Zwager, Charlotte L.; Francis, Jane M.; Aye, Christina Y.L.; Williamson, Wilby; Neubauer, Stefan; Leeson, Paul
Abstract : Introduction: Increased blood pressure (BP) variability is a cardiovascular risk marker for young individuals and may relate to the ability of their aorta to buffer cardiac output. We used a multimodality approach to determine relations between central and peripheral arterial stiffness and BP variability. Methods: We studied 152 adults (mean age of 31 years) who had BP variability measures based on SD of awake ambulatory BPs, 24-h weighted SD and average real variability (ARV). Global and regional aortic distensibility was measured by cardiovascular magnetic resonance, arterial stiffness by cardio-ankle vascular index (CAVI) and pulse wave velocity (PWV) by SphygmoCor (carotid–femoral) and Vicorder (brachial–femoral). Results: In young people, free from overt cardiovascular disease, all indices of SBP and DBP variability correlated with aortic distensibility (global aortic distensibility versus awake SBP SD: r  = −0.39, P  < 0.001; SBP ARV: r  = −0.34, P  < 0.001; weighted 24-h SBP SD: r  = −0.42, P  < 0.001). CAVI, which closely associated with aortic distensibility, also related to DBP variability, as well as awake SBP SD ( r  = 0.19, P  < 0.05) and weighted 24-h SBP SD ( r  = 0.24, P  < 0.01), with a trend for SBP ARV ( r  = 0.17, P  = 0.06). In contrast, associations with PWV were only between carotid–femoral PWV and weighted SD of SBP ( r  = 0.20, P  = 0.03) as well as weighted and ARV of DBP. Conclusion: Greater BP variability in young people relates to increases in central aortic stiffness, strategies to measure and protect aortic function from a young age may be important to reduce cardiovascular risk.